Healthcare Workers’ Roles and Iron Tablet Adherence among Pregnant Women: A Prospective Cohort Study - MS, Sri Wahyuni; Nova Ratna Dewi; Hida Yana (Community Medicine and Education Journal, 2024)
Iron deficiency anemia during pregnancy poses significant health risks to both mother and child. The role of healthcare workers in promoting iron tablet adherence is crucial. This study aimed to analyze the influence of healthcare workers' roles (as customer, communicator, motivator, facilitator, and counselor) on pregnant women's adherence to iron tablet consumption. A prospective cohort study was conducted involving pregnant women within the Puskesmas Lut Tawar work area in Aceh Tengah District. Data collection included questionnaires and interviews. The study assessed the relationship between healthcare workers' roles and adherence to iron tablet consumption using statistical analysis. The study found that the role of healthcare workers as counselors had a significant influence on adherence to iron tablet consumption (P = 0.041). Other roles, such as customer, communicator, motivator, and facilitator, did not show a statistically significant impact on adherence. The role of healthcare workers as counselors plays a crucial role in improving pregnant women's adherence to iron tablet consumption. The study recommends enhancing the counseling skills of healthcare workers and providing comprehensive support to pregnant women to address their concerns and challenges related to iron tablet intake.